The Profile of a Teaching Assistant in the Context of Personality Traits in the Olomouc Region - Dockalova, Justyna; Kvintova, Jana; Hajkova, Radka; Dobesova Cakirpaloglu, Simona (e-Pedagogium, 2023)
The paper focuses on teaching assistants and their profile in the context of personality traits. The aim of the study is to describe and examine the distribution of personality traits among teaching assistants in the Olomouc Region. Their personality traits were examined using the NEO Personality Inventory. The inventory was part of an online battery which was sent by email to all elementary schools in the Olomouc Region. We obtained a research sample of 159 respondents. The result is a description of personality traits among teaching assistants in the Olomouc Region. Compared with the standard, a statistically significant difference was confirmed in the dimensions of openness to experience, neuroticism, conscientiousness and agreeableness. In terms of extraversion, no statistically significant difference was observed. In the conclusion section, the results are put into context with other professions.
Keywords: teaching assistant; personality traits; Olomouc Region.